2014
DOI: 10.1016/j.jallcom.2013.12.125
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of negative capacitance effect in (CoFeZr)x(CaF2)(100−x) nanocomposite films deposited by ion beam sputtering in argon and oxygen atmosphere

Abstract: The paper presents frequency f and temperature T p dependences of phase shift angle H, admittance r and capacitance C p for the as-deposited and annealed (CoFeZr) x (CaF 2 ) (100Àx) nanocomposite films deposited by ion-beam sputtering of a compound target in a mixed argon-oxygen gas atmosphere in vacuum chamber. The studied films presented metallic FeCoZr ''cores'' covered with FeCo-based oxide ''shells'' embedded into oxygen-free dielectric matrix (fluorite). It was found for the metallic phase content within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…While nitrides of single elements are studied well enough, their multilayer modifications need study that is more detailed [26][27][28][29][30][31][32][33][34][35]. Therefore, the study of features of structure, elemental and phase composition of multilayer coatings depending on the deposition conditions is an important task in solid-state physics and materials science [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…While nitrides of single elements are studied well enough, their multilayer modifications need study that is more detailed [26][27][28][29][30][31][32][33][34][35]. Therefore, the study of features of structure, elemental and phase composition of multilayer coatings depending on the deposition conditions is an important task in solid-state physics and materials science [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Coating deposition parameters, such as the substrate temperature, the flow rate, the energy of atoms and ions incident on the surface of the growing coating, and the deposition rate, have a significant effect on the chemical composition and structure of the coating. It was found that it is necessary to provide a high substrate temperature [53,54] or introduce impurities [8,[55][56][57][58][59][60]] to obtain a superconducting phase of NbN with a critical temperature of about 16 K. The main feature of the currently available magnetron sputtering method [9][10][11] is the possibility of depositing coatings without introducing impurities or heating the substrate to high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Composites composed of ferromagnetic nanoparticles set in a dielectric matrix make an example of such materials. Matrices are the most often made of very stable dielectrics in the form of metal oxides such as Al 2 O 3 [1][2][3] or SiO 2 [4][5][6][7] or of non-oxide dielectrics (oxygen-free matrices) like fluorides CaF 2 [8][9][10] as well as of ferroelectric materials PZT [11][12][13] or materials of low conductivity [14].…”
Section: Introductionmentioning
confidence: 99%